Ananlysis of Nickel Chelate solution with m-Chloroazo-antipyrine and Determination of Trace Amounts of Nickel in Wastewater - Gao, Hong-Wen; Zhang, Peng-Fei (Asian Journal of Chemistry, 2010)
The chelate of Ni with m-chloroazoantipyrine (CAA) has been studied. Its characteristic factors were analysed for example, instability constant, complexation ratio and practical molar absorptivity. The new usage of β-correction principle has been built here. By means of the disscused ligand, the determination of trace amounts of nickel has been improved at pH 6. Results showed that Ni/CAA = 1:2 in their chelate, its practical molar absorptivity was equal to 3.52 x 104 L. mol–1 cm–1 at 630 nm and its total instability constant to 3.62 x 10–12 at pH 6 and 32ºC with ions strength equal to 0.1. The analysis to wastewater show that the recovery of Ni was between 92.0 and 111 % and the relative standard deviations less than 3.8%.